Determination of Carboxypeptidase Activity in Clinical Pathogens by Gas Chromatography–Mass Spectrometry. (23rd May 2016) - Lough, Fraser; Perry, John D.; Stanforth, Stephen P.; Dean, John R.
ABSTRACT: A novel method for the determination of benzoic acid has been employed to identify carboxypeptidase activities in clinically relevant pathogens. Benzoic acid was determined after chemical derivatization by gas chromatography–mass spectrometry (GC–MS). N-Benzoyl amino acid substrates were evaluated for the detection of carboxypeptidase activities in a number of clinical pathogens. Upon enzymatic hydrolysis of these substrates, benzoic acid was produced which was detected by extraction from the liquid culture supernatant, derivatization as the trimethylsilyl ester, with subsequent analysis by GC–MS. Enzymatic hydrolysis of N-benzoyl glycine was observed for S. agalactiae, M. morganii, and A. baumannii . In addition, P. fluorescens was found to hydrolyze N-benzoyl-L-glutamic acid. Although the method provides an alternative approach for determining carboxypeptidase activity, ultimately it would not be a suitable method in a clinical setting. However, the method is well-suited for identifying carboxypeptidase activities that have not been previously described or to corroborate a carboxypeptidase assay with the ninhydrin reagent.